EOCENE STALKED CRINOIDS IN THE GENUS ISSELICRINUS (ECHINODERMATA, CRINOIDEA, ISOCRINIDA) FROM NORTHEASTERN ITALY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2024)
Long fragments of isocrinid stalks belonging to the stalked crinoid genus Isselicrinus (Isocrinida, Isselicrininae) were found at Cambrigar, near Ferrara di Monte Baldo (Verona province, northeastern Italy) in the strata called “Harpactocarcinus punctulatus and Pentacrinus diaboli horizon”, traditionally ascribed to the lower Eocene (Ypresian). Morphometric analysis of this material allowed us to identify two distinct species filtering their food at different levels of the water column. The first species, characterized by a mostly pentagonal stalk section, is ascribable to Isselicrinus diaboli (Bayan), a taxon frequently cited from the lower Eocene of northeastern Italy but until now poorly known. The other species has a marked star-shaped stalk section presenting a combination of pedomorphic characters and is ascribed to the new taxon Isselicrinus baldoensis n. sp. A detailed analysis of numerous columnals and pluricolumnals of Isselicrinus diaboli from the type-locality of San Pancrazio near Mossano (Berici Hills, Vicenza province, northeastern Italy) allowed us to propose a revised and more complete diagnosis of this taxon. The particular burial conditions and the ecology of these two species are discussed as well as a reappraisal of the age of the “Harpactocarcinus punctulatus and Pentacrinus diaboli horizon”. Based on new calcareous nannofossil data, and confirmed by the larger foraminiferal assemblages, the isocrinids from Cambrigar are firmly assigned to the Lutetian (middle Eocene). Calcareous nannofossils identified in the matrix of historical hand specimens from the classical locality of San Pancrazio indicate a similar age.
Keywords: Echinodermata, Crinoidea, Isocrinida, Isselicrinus diaboli, middle Eocene, new species, paleoecology, taxonomy, taphonomy